The Relationship Therapeutic Communication With Level Anxiety Of The Patient's Family In The Intensive Care Unit. - Hasiolan, Mara Imbang Satriawan; Irwanto, Moh Firman (PT. Nursing Genius Care, 2024)
Type here, write the abstract in Indonesian, maximum 250 words and structured including: Background, Objectives, Methods, Results and Conclusions. Background: The intensive care unit is a special room equipped with special medical equipment, and provided by the hospital to treat patients with conditions that require close supervision. Nurses' skills in communicating can help patients and their families communicate thoughts and feelings more effectively. Purpose: This study aims to explore the relationship between therapeutic communication and the anxiety level of families of patients treated in the Intensive Care Unit. Methods: This is quantitative research with a correlational design. The sampling used was purposive sampling, with inclusion and exclusion criteria totaling 71 people. The instrument used is a questionnaire. Results: The results showed that the majority of respondents were adults 83.1% (n=59), high school education 73.3% (n=52), and male 76.1% (n=54). Family experience of being treated in the ICU was never 98.5% (n=68). The therapeutic communication is good 73.2% (n=52), level of anxiety is moderate 69.0% (n=49). p-value 0.036 < (α=0.05), there is a significant relationship between therapeutic communication and the patient's family's anxiety level in the intensive care unit. Conclusion: Implementing effective communication strategies can provide a better understanding of the patient's condition, and involve the family in the care process. Therefore, developing therapeutic communication skills among medical personnel should be a priority to improve the quality of care in the ICU.